Estimulação transcraniana na disartria decorrente da doença de Parkinson: estudo de casos - Rosa, Rafaela Rossini (2022)
Parkinson's disease (PD) is the second most common neurodegenerative disease in adults aged 60 years . PD diagnosis is clinical and based on the symptoms: resting tremor, stiffness, bradykinesia, and impaired postural balance. Motor speech subsystems disorders are also common in PD, named dysarthria. Transcranial direct current stimulation (tDCS) is a non-invasive and cost-effective option compared to deep brain stimulation in therapeutic resources for PD Studies show that tDCS promotes improvements in Parkinson's global motors. However, there are no studies that research this technique in dysarthria cases. Thus, this present study aimed to compare the results of different treatment designs for dysarthria in subjects with PD, involving conventional speech therapy and tDCS and a control. It is an analytical, observational, transversal, descriptive, interventional, and quantitative research. Four male subjects with PD (aged between 68 and 79), were evaluated and re-evaluated with the Dysarthria Assessment Protocol, Speech Intelligibility Assessment Protocol, the Consensus auditory-perceptual evaluation of voice, and by glottal source acoustic analysis. Each subject was assigned a different study design: a control subject (S1); one submitted to 10 sessions of 20 minutes of tDCS (S2); one submitted to 10 sessions of 20-minute sessions of tDCS and conventional speech therapy for concomitant dysarthria (S3); and one to 25 sessions of 50-minutes of conventional speech therapy (S4). Effects immediately after the last session and after 30 days were analyzed. All speech subsystems improved in subjects who received some intervention. S2 had more improvements in the phonation time task, velar movement, and dysarthria evaluation, followed by S3. In the acoustic vocal analysis of glottic source, the standard deviation of the fundamental frequency, maximum fundamental frequency, Jitter, Shimmer, and noise measurementsimproved with some intervention, especially at S3 in the immediate post-intervention assessment and 30 days after, followed by S2, in the immediately post-intervention evaluation. However, only conventional therapy made it possible to change the dysarthria severity. Conventional speech therapy combined with the tDCS, and therapy with tDCS alone had more impact on speech and voice than conventional therapy alone.